THE EFFECT OF SOLVABILITY (DAR) AND PROFITABILITY (ROA) TOWARD STOCK PRICES (Empirical Study of Consumer Goods Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the period of 2016-2018) - Mulyawan, Ferry; Genia Fatihat, Gita; Indah Bayunitri, Bunga (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the effect of DAR and ROA variables on stock prices partially and simultaneously on the manufacturing companies in the consumer goods industry sector. Secondary data in the form of an overview of the financial statements of 16 manufacturing companies in the consumer goods industry sector from 2016 to 2018. The research method uses the classic assumption test and multiple linear regression with SPSS version 20.00. The results of the t-hypothesis test show that the debt to asset ratio variable has no effect on stock prices, while the return on asset variable has a significant effect on stock prices. Hypothesis f-test results indicate that simultaneously these two variables also showed a significant influence on firm value. The R-square value is 0.159, which means that the debt to asset ratio and return on asset variables are able to explain the company’s value variable by 15.9%, while the rest can be influenced by other factors not included in this research model.